Analisis Faktor - Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan-Perusahaan yang Terdaftar Dalam Indeks LQ45 di Bursa Efek Indonesia - Listari, Sinta (Jurnal Ilmiah Manajemen Kesatuan, 2018)
Corporate value is very important for a company to achieve its main objectives. Companies always want to increase their values to look expensive sothat investors are willing to invest funds in them. Increased corporate value is influenced by many factors both from fundamental factors and technical factors.Fundamental factors come from within a company such as growth opportunity, profitability, capital structure, ownership structure, and firm size. While technicalfactors come from outside the company such as volume and frequency of stock trading in the stock market. The higher the resulting factor the higher the value of the company produced.Based on the results of research and discussion it can be seen that in the results of Bootstrap Test Coefficient of Company Value Construct Line, Growth Opportunity variables measured using IOE, INVOS, PER, MBTA, and MBTE show that MBTA and MBTE have a positive and real effect on Growth Opportunity. Profitability variables measured by using ROA and ROE indicate that Profitability is influenced significantly by ROA and ROE Variable GrowthOpportunity have a positive and significant impact on company value. All exogenous variables (Capital Structure, Ownership Structure, Company Size,Trade Volume, Frequency of Trade) have no effect on Corporate Value. Corporate Value Variability can be explained by the Capital Structure, Size Ownership Structure, Trading Volume and Trading Frequency of 99.2% and the rest of 0.8% explained by other variables.